A novel alveolate-structured organic-inorganic hybrid with high activity for photocatalytic hydrogen evolution. (5th May 2020) - Ying, Guo-Gang; Guo, Si-Yao; Chen, Li-Ping; Chen, Ji-Zhou; Li, Ying; Wang, Huan-Li; Liu, Yang
Abstract: Organic-inorganic hybrid nano-material has a significant potential for enhancing the charge separation efficiency of photocatalyst. However, it remains an important issue to controllable synthesis new hybrid system with unique structure and earth-abundant materials for boosting photocatalytic hydrogen revolution. We report a facile one-step hydrothermal strategy to fabricate a novel Titania/β-cyclodextrin (TiO2 /β-CD) organic-inorganic hybrid nano-material with an alveolate structure. In this hybrid system, β-CD not only played a critical role in alveolate structure formation, but also served as a bridge connecting target molecular and active sites on the TiO2 surface to facilitate the separation and transfer of the photoexcited electrons with prolonged lifetime. As a result, this alveolate TiO2 /β-CD composite exhibited outstanding photocatalytic activity and a H2 evolution rate of 725 μmol/g·h was achieved over TiO2 /β-CD which was 14 times of bare TiO2 under simulated sunlight. This work paves a way for controllable synthesis of novel organic-inorganic hybrid nano-material with distinct structure for efficient photocatalysis. Graphical abstract: Image 1 Highlights: A novel alveolate organic-inorganic hybrid has been successfully prepared. The hybrid composite exhibited outstanding photocatalytic activity. The H2 evolution rate of TiO2 /β-CD has a good durability. This work paves a way for controllable synthesis of organic-inorganic TiO2 . Limited reports on the photocatalytic water splitting of the TiO2 /β-CD.